Fase de la planificación de la auditoría al componente cuentas y documentos por cobrar Guayas S.A. periodo 2018. - Sabando Hidalgo, Maria Gabriela (My University, 2019)
Companies to maintain an efficient management of their economic activities must have internal controls that contribute to safeguarding the financial interests of the organization. To achieve this, the development of financial audits is necessary to detect errors or shortcomings of the different accounts or accounting components. The identification of these types of audit risks involves developing a planning that guides the auditor during his investigation. This would be the problem of the company Guayas S.A. that you need to know the reality of the accounts and documents receivable component of the year 2018, following the International Audit Standards (NIA) that serves to carry out a work program that helps to directly plan the audit report, based on the exclusive policies, procedures and guidelines of the company. Information that will serve for the correct decision making by management. The general objective is to prepare a financial audit for the internal control of the accounts and receivables component of the company Guayas S.A. 2018 period. The methodological procedure applied will be the descriptive and analytical one in order to perform an examination of the accounts receivable component. The technique used was the literature for which scientific articles and information books were accessed that served as a guide for the development of the research.
Las empresas para mantener una gestión eficiente de sus actividades económicas deben de contar con controles internos que contribuyan a salvaguardar los intereses financieros de la organización. Para lograrlo es necesario el desarrollo de auditorías financieras para detectar errores o falencias de las diferentes cuentas o componentes contables. La identificación de estos tipos de riesgos de auditoría implica elaborar una planificación que guía al auditor durante su investigación. Este sería el problema de la empresa Guayas S.A. que necesita conocer la realidad del componente cuentas y documentos por cobrar del año 2018, rigiéndose a las Normas Internacionales de Auditoría (NIA) que sirva para llevar a cabo un programa de trabajo que ayude a la planificación directa del informe de auditoría, basándose en las políticas, procedimientos y directrices exclusivos de la empresa. Información que servirá para la correcta toma de decisiones por parte de la gerencia. El objetivo general es elaborar una auditoría financiera para el control interno del componente cuentas y documentos por cobrar de la empresa Guayas S.A. periodo 2018. El procedimiento metodológico aplicado será el descriptivo y analítico para poder realizar un examen al componente cuentas por cobrar. La técnica utilizada fue la bibliográfica para lo que se accedió a artículos científicos y libros información que sirvió de guía para el desarrollo de la investigación.
Keywords: AUDITORIA FINANCIERA; CONTROL INTERNO; PLANIFICACIÓN; RIESGO; CUENTAS Y DOCUMENTOS POR COBRAR